2022
DOI: 10.1021/acssuschemeng.1c06314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steam Injection during Carbonation on the Multicyclic Performance of Limestone (CaCO3) under Different Calcium Looping Conditions: A Comparative Study

Abstract: This study explores the effect of steam addition during carbonation on the multicyclic performance of limestone under calcium looping conditions compatible with (i) CO 2 capture from postcombustion gases (CCS) and with (ii) thermochemical energy storage (TCES). Steam injection has been proposed to improve the CO 2 uptake capacity of CaO-based sorbents when the calcination and carbonation loops are carried out in CCS conditions: at moderate carbonation temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…The reversible nature of the reaction is a key functionality of this reaction system accompanied by release/adsorption of CO 2 and endothermic/exothermic changes, which has recently focused on establishing the most effective Ca-looping system for energy storage and CO 2 capture technologies. Kinetic behavior of the thermal decomposition of CaCO 3 is characterized by the significant effect of atmospheric CO 2 . Under linearly increasing temperature conditions at a fixed heating rate (β), thermogravimetry (TG)–derivative TG (DTG)–differential thermal analysis (DTA) curves for the thermal decomposition of CaCO 3 shift systematically to higher temperatures with increasing the partial pressure of CO 2 ( p (CO 2 )) in the reaction atmosphere (Figure ), in which the shift of the reaction initiation temperature is more significant compared with that of the reaction ending temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The reversible nature of the reaction is a key functionality of this reaction system accompanied by release/adsorption of CO 2 and endothermic/exothermic changes, which has recently focused on establishing the most effective Ca-looping system for energy storage and CO 2 capture technologies. Kinetic behavior of the thermal decomposition of CaCO 3 is characterized by the significant effect of atmospheric CO 2 . Under linearly increasing temperature conditions at a fixed heating rate (β), thermogravimetry (TG)–derivative TG (DTG)–differential thermal analysis (DTA) curves for the thermal decomposition of CaCO 3 shift systematically to higher temperatures with increasing the partial pressure of CO 2 ( p (CO 2 )) in the reaction atmosphere (Figure ), in which the shift of the reaction initiation temperature is more significant compared with that of the reaction ending temperature.…”
Section: Introductionmentioning
confidence: 99%
“…) , and sophistication of the reaction conditions (heating–cooling programs, atmospheric conditions, etc. ). An advanced understanding of the heterogeneous kinetics of the forward and reverse reactions in eq can strongly support the establishment of a more sophisticated Ca-looping system for CO 2 absorption and thermal energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of steam in the carbonation atmosphere effectively improves the heat storage performance of the calcined limestone. Troya et al 53 studied the cyclic heat storage performance of limestone carbonated under 19% steam/81% CO 2 at 850 °C and found that the introduction of steam in the carbonation atmosphere could not improve the effective conversion of limestone. In this work, the introduction of steam decreases the exothermic temperature, and the low temperature retards the sintering of CaO.…”
Section: Resultsmentioning
confidence: 99%
“…The limestone calcined under steam and carbonated under 20% steam/80% CO 2 exhibits the highest BET surface area and BJH pore volume, 3.72 m 2 g −1 and 0.0156 cm 3 g −1 , respectively. Arcenegui-Troya et al 24,53,55 performed heat storage tests in a fixed bed reactor and found that steam in the calcination stage and carbonation stage improved the surface structure of the calcined limestone to facilitate the heat storage performance of the limestone. Their results are consistent with those in this work.…”
Section: Resultsmentioning
confidence: 99%